In situ excitation of BODIPY fluorophores by 89Zr-generated Cerenkov luminescence. Issue 83 (29th September 2022) - Gristwood, Katie; Luli, Saimir; Rankin, Kenneth S.; Knight, James C.
Abstract : Secondary Cerenkov-induced fluorescence imaging (SCIFI) is an emerging optical imaging modality that affords high signal-to-noise images. This report examines the utility of BODIPY fluorophores in SCIFI applications using 89 Zr-generated Cerenkov luminescence. Abstract : Secondary Cerenkov-induced fluorescence imaging (SCIFI) is an emerging optical imaging technology that affords high signal-to-noise images by utilising radionuclide-generated Cerenkov luminescence to excite fluorescent probes. BODIPY dyes offer attractive properties for SCIFI, including high quantum yields and photochemical stability, yet their utility in this application in combination with clinically relevant β + -emitting radioisotopes remains largely unexplored. In this report, the fluorescence properties of three meso -substituted BODIPY analogues have been assessed in combination with the positron emitter zirconium-89. Most notably, SCIFI data acquired over 7 days shows the BODIPY scaffold remain largely inert to radiolysis, indicating the promising utility of this fluorophore class in SCIFI applications.